A Brief Review of Hydrogels for Drug Delivery for Different Organs of the Body: Synthesis, Categorization, and Organ-Specific Applications - Azadeh Asefnejad; Nesa Rastgoo; Shirin Ardeshiriansharifabadi; Samira Basir Shabestari; Tohid Khodadadi; Foad Iranmanesh (Nanochemistry Research)
Hydrogels have emerged as a promising class of biomaterials for drug delivery applications due to their unique physicochemical properties, including high water content, soft and rubbery texture, and ability to encapsulate and release therapeutic agents in a controlled manner. This review article provides a comprehensive overview of the synthesis, types, and applications of hydrogels in various organs of the body for drug delivery. The article first discusses different methods of hydrogel synthesis, including physical, chemical, and enzymatic crosslinking techniques, and how these influence the final properties of the hydrogel. It then categorizes hydrogels based on their source (natural or synthetic), responsiveness to stimuli (e.g., pH, temperature, light), and structural characteristics (e.g., interpenetrating networks, hybrid hydrogels). The article subsequently explores the utilization of hydrogels for drug delivery in diverse anatomical locations, such as the skin, eyes, nasal and oral cavities, gastrointestinal (GI) tract, and cardiovascular system. It shows how the unique features of hydrogels, such as high biocompatibility, tunable degradation kinetics, and the ability to incorporate various therapeutic agents, making them well-suited for targeted and controlled drug release in these organs. Finally, the article discusses the current challenges and future prospects in the field of hydrogel-based drug delivery systems (DDS), including the need for advanced characterization techniques, scale-up manufacturing, and clinical translation. This article represents a valuable resource for researchers, clinicians, and pharmaceutical scientists interested in leveraging the potential of hydrogels for innovative drug delivery solutions.